Blood perfusion and microenvironment of human tumors : implications for clinical radiooncology / M. Molls, P. Vaupel, (eds.) ; with contributions by J.M. Brown [and others] ; foreword by L.W. Brady and H.-P. Heilmann.
Summary goes here